The Role of School Supervisors in Supporting the Flagship Character Education Development Program at Elementary School - Tulus Bintoro; Nur Khoiri; Widya Kusumaningsih (Papanda Publisher, 2026)
This study examined the role of school supervisors in assisting the implementation of the flagship character education development program at SD Negeri 1 Depok, Grobogan Regency, during the 2025/2026 academic year. Despite growing recognition of supervisory functions in school quality improvement, empirical evidence on how supervisors operate within structured, government-mandated character education programs at the elementary level remains limited. This study employed a qualitative case study design. Data were collected through semi-structured interviews, classroom observations, and document analysis involving five participants — one school supervisor, one principal, and three teachers — and analyzed using Miles et al.'s (2014) interactive model. Four themes emerged: systematic program planning, collaborative supervisory assistance, structured follow-up actions, and positive impact on students' character development. An unexpected finding was the emergence of peer-to-peer character reinforcement among students, suggesting that sustained supervisory engagement may facilitate value internalization beyond the teacher–student dyad. These findings demonstrate that supervisory assistance, when conducted collaboratively and continuously, constitutes a transformative institutional mechanism for character education. The study contributes to educational supervision scholarship and offers practical guidance for supervisors and policymakers in strengthening elementary character education programs.